2015
DOI: 10.1039/c5ob01383f
|View full text |Cite
|
Sign up to set email alerts
|

Construction of benzo-fused indolizines, pyrrolo[1,2-a]quinolines via alkyne–carbonyl metathesis

Abstract: The strategic use of a sequential Sonogashira coupling/intramolecular alkyne-carbonyl metathesis process for the synthesis of a pyridine ring from 1-(2-haloaryl)-1H-pyrrole-2-carbaldehydes allowed ready access to diverse novel benzo-fused indolizines, pyrrolo[1,2-a]quinolines, in good to excellent yields. As a hybrid structure of indolizine and quinoline, the resulting scaffold has an acyl substituent at the C5 position, which is difficult to make by any other known approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…These include palladium-catalyzed reactions, [14][15][16][17] 1,2-alkyl migration, 18 DDQ-mediated intramolecular cyclizations, 19 flash vacuum pyrolysis, 20 photosubstitution reactions, 21 and alkynecarbonyl metathesis. 22 Lautens et al reported a palladium catalyzed direct arylation of geminal dibromo-olefins with a boronic acid via tandem Suzuki-Miyura coupling reaction. 23 Larock et al reported a copper catalyzed tandem synthetic methodology for the synthesis of pyrrolo-and indolo[2,1-a]isoquinolines.…”
mentioning
confidence: 99%
“…These include palladium-catalyzed reactions, [14][15][16][17] 1,2-alkyl migration, 18 DDQ-mediated intramolecular cyclizations, 19 flash vacuum pyrolysis, 20 photosubstitution reactions, 21 and alkynecarbonyl metathesis. 22 Lautens et al reported a palladium catalyzed direct arylation of geminal dibromo-olefins with a boronic acid via tandem Suzuki-Miyura coupling reaction. 23 Larock et al reported a copper catalyzed tandem synthetic methodology for the synthesis of pyrrolo-and indolo[2,1-a]isoquinolines.…”
mentioning
confidence: 99%
“…[182] The intramolecular alkyne-aldehyde metathesis of 1-(2-haloaryl)-1Hpyrrole-2-carbaldehydes, catalyzed by trifluoroacetic acid, gave benzo-fused indolizines 131 (Table 5, entry 9). [183] Indolizine-1carbaldehyde derivatives 132 were obtained in good yields via a 1,3-dipolar cycloaddition of phenylpropiolaldehydes promoted by cesium carbonate (Table 5, entry 10). [184] 10.…”
Section: Transition Metal-free Synthesis Of Indolizinesmentioning
confidence: 99%
“…84 The parent pyrrole derivative 87 was prepared via Sonogashira coupling and subsequently transformed into the desired indolizine by heating in TFA. 84 The parent pyrrole derivative 87 was prepared via Sonogashira coupling and subsequently transformed into the desired indolizine by heating in TFA.…”
Section: Scheme 54mentioning
confidence: 99%